Caracterização molecular dos microrganismos produtores de aromas em cafés fermentados - Demito, Matheus Lopes (2019)
Coffee is responsible for 13.5% of GDP in Minas Gerais and has a rise in studies that may contribute to the value of coffee and make it a product considered as special. This case, biotechnology emerges as a tool capable of supporting the development of bioprocesses for the production of this product and supplying this demand, also contributing to a current indispensability of sustainable production. For this purpose, the isolation and characterization of the microorganisms that produced aromas of samples of Minas Gerais coffee were carried out. After sequencing, the treatment of information with software BioEdit 2.0 is an information identification tool for data collection (NCBI). The top lineages were: Geotrichum candidum, Galactomyces candidus, Pichia membranifaciens, Pichia kudriavzevii and Pichia fermentans. Therefore, a biotechnological tool that can be used to enhance coffee end products is the addition of fungus-produced bioarms.